Digital Marketing Strategies to Enhance Bank Competitiveness in the Technology Disruption Era - Kanzun, Fatna (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This research explores technology-based digital marketing strategies implemented by state-owned banks (bank BUMN) to enhance competitiveness in technological disruption. Using a qualitative approach and case research method, the research identifies the critical roles of technologies such as artificial intelligence (AI), big data analytics, and customer relationship management (CRM) systems in creating personalized and relevant customer experiences. The findings reveal that social media, mobile banking applications, and email marketing are the primary channels used in digital marketing strategies. Social media effectively increases brand awareness, while mobile banking applications maintain customer loyalty through interactive features. However, significant challenges such as internal resistance, technological infrastructure limitations, and a lack of cross-departmental coordination hinder these strategies’ implementation. To address these challenges, the research recommends investments in technological infrastructure, staff training, and fostering an adaptive organizational culture to change. These findings provide theoretical contributions by supporting previous literature highlighting the importance of digital technology in marketing and practical contributions in strategic recommendations for state-owned banks. Thus, this research offers in-depth insights into how digital technology can holistically enhance competitiveness and customer experience.